(untitled) (Journal of Engineering, 2025)
This study evaluates the performance of Self-Compacting Engineered Cementitious Composites (SCC-ECC) under standard 28-day water curing, aiming to develop a mixture with optimal flowability, high mechanical strength, and enhanced durability. Twenty-seven SCC-ECC mortar mixtures (without coarse aggregate) were prepared and tested according to EFNARC (2002) guidelines for self-compacting mortars. Fresh results (slump flow 240–260 mm, V-funnel 6–12 s, L-box >0.80) confirmed adequate flowability. In addition, direct tensile tests on dog-bone specimens demonstrated strain-hardening with multiple fine cracks and strain capacity exceeding 2%, verifying the ECC behavior. The mixtures were prepared with varying fly ash contents (20%, 25%, 30%), polyvinyl alcohol (PVA) fibers (1.5%–2.0%), and a high-range water-reducing admixture. The optimal mixture (R2) was identified based on superior results in compressive strength, flexural strength, impact resistance, water permeability, and elastic modulus. The selected mixture achieved compressive strength exceeding 70 MPa, flexural strength above 14 MPa, and impact energy absorption over 17,000 J, with very low chloride permeability (<750 Coulombs). Scanning Electron Microscopy (SEM) analysis confirmed a dense matrix and strong fiber–matrix bonding. The results demonstrate the feasibility of producing SCC-ECC with excellent fresh and hardened properties using industrial by-products and performance-enhancing additives, supporting the development of sustainable, high-performance composites for structural applications in aggressive environments.